2015
DOI: 10.14569/ijarai.2015.040903
|View full text |Cite
|
Sign up to set email alerts
|

A Directional Audible Sound System using Ultrasonic Transducers

Abstract: Abstract-In general the audible sound has the characteristics of spreading, however the ultrasound is directional. This study used amplitude-modulating technique for an array of 8 ultrasonic transducers to produce directional audible sound beam. In this study sound field distribution for the directional audible sound beam has been investigated. The effect of different weightings varied with different frequency for the transducers on the directivity of the sound beam has also been evaluated. An optimization met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The ultrasonic sensor block provides the input for the microcontroller. Ultrasonic is sound with a frequency greater than the upper limit of human hearing (greater than 20 kHz) [12,13]. The speed of sound depends on the medium the waves pass through, and is a fundamental property of the material.…”
Section: Ultrasonic Sensormentioning
confidence: 99%
“…The ultrasonic sensor block provides the input for the microcontroller. Ultrasonic is sound with a frequency greater than the upper limit of human hearing (greater than 20 kHz) [12,13]. The speed of sound depends on the medium the waves pass through, and is a fundamental property of the material.…”
Section: Ultrasonic Sensormentioning
confidence: 99%
“…Previous work has shown that host-level attacks can be mounted via sensor saturation [21], [18], [16] or by exploiting the impact of adversarial inputs on machine-learning techniques [9], [17], [10], [19], [4]. Up until now, no techniques have been proposed as to how attacks on individual hosts can be scaled.…”
Section: E Tactical Aspectsmentioning
confidence: 99%
“…Directional ultrasound acoustic jammers consist of an array of powered ultrasound transducers whose output is focused into a narrow beam with a distance range of a few tens of meters [21]. These were developed with (a short range) for medical imaging and (medium range) for sound entertainment systems [18]. Such precision engineering tools can be repurposed as attack tools to shine an acoustic spotlight to stealthily saturate vehicles deploying sonars.…”
Section: Introductionmentioning
confidence: 99%